Table of Contents - Morris, Melissa (The Motley Undergraduate Journal, 2023)
Acknowledgements MELISSA MORRIS p. 3 Letter From the Editor MARIA BAKARDJIEVA p. 5 The Motley Editorial Team p. 7 Meet the Authors p. 11 Research and Analytical Articles Frederick Douglass: Visibility of a visionary ARIADNA ALVARADO p. 14 The face of Orientalism: The western appropriation and commodification of Asian culture ABIGAIL ATMADJA p. 26 Performing Muslim identities through embodiment- Self-representing through fashion, aesthetics, and style ASMA BERNIER p. 38 The contemporary aesthetics of adolescence: How Euphoria uses style to spectacularize representation of modern youth in the articulation of a teenage gaze LANA COLES p. 58 Sigma male grindset as alienation and asceticism: A rejection of individual emancipation in the work of Karl Marx CLAIRE HADFORD p. 82 Can the line cook speak: A critical discourse analysis of the voice and representation of Canadian restaurant staff during the Covid-19 pandemic BRAY JAMIESON p. 96 Kidfluencers and conundrums: The rising need for Internet policy that addresses child labour and safety MELISSA MORRIS p. 116 History of Transnational cinema and feminist film theory: Understanding the potential of Transnational women’s film ASHA SARA p. 128 Creative Research A visual rhetorical analysis of Queer visibility strategies active in contemporary American television MADISON DANIELS p. 135 EN-LIGHTEN-ED: The politics of Black hair GLORY OKELEKE p. 136 Archaic methods, subculture sensibilities, outside aesthetics & Instagram: A humble cultural artifact attempts to resist the almighty algorithm CALUM ROBERTSON p. 137